Fungicide Resistance Action Committee's (FRAC) Classification Scheme of Fungicides According to Mode of Action - Frederick M. Fishel (EDIS, 2009)
Revised! PI-94, a 9-page guide by Frederick M. Fishel, addresses resistance to pesticides and describes the Fungicide Resistance Action Committee’s (FRAC) classification of fungicides and bactericides registered for use in Florida by their modes of action. A cross reference of common names for active ingredients — with corresponding examples of their trade names — is also provided. Includes sources of additional sources. Published by the UF Department of Agronomy, January 2009.